Optimization of sensor selection problem in IoT systems using opposition-based learning in many-objective evolutionary algorithms. (January 2022) - Younas, Irfan; Naeem, Ameera
Abstract: In the Internet of Things (IoT) systems, physical objects are connected to each other through sensor devices that serve multiple functionalities. The sensor selection is known to be an NP-hard problem. Thus, Evolutionary Algorithms (EAs) can be incorporated to solve the sensor selection problem in IoT systems. Previously, researchers have been working on sensor selection problems with two or three objectives. Recently, this problem is formulated as a many-objective optimization problem and solved using a Decomposition-based Many-Objective Evolutionary Algorithm (MOEA/D). In this paper, we consider the sensor selection problem as a many-objective problem with 5 objectives. To accelerate the convergence, we incorporate Opposition Based Learning (OBL) in the general framework of MOEA/D. Furthermore, we use a well-known many-objective algorithm known as the Non-dominated Sorting based Genetic Algorithm incorporated with OBL (NSGA-III/OBL) to enhance its convergence and diversity. The experimental results show that NSGA-III/OBL outperforms all other compared algorithms. Graphical abstract: Highlights: The sensor selection is considered as a many-objective problem with 5 objectives. Opposition-based many-objective optimizer is proposed to solve the problem. The proposed approach results in better convergence and diversity of the solutions. The NSGA-III/OBL outperforms all other compared algorithms.